The Idea of Implementing AI into the Learning Management System - Samudra, Jimmy Prawira; Liang, Wisely; afandi, afandi (Journal of Information System and Technology (JOINT), 2024)
This academic research paper is intend to propose our team ideas into upcoming future society named society 5.0. We will be researching in how Artificial Intelligence (AI) can provide its technologies capabilities into Learning Management System (LMS). LMS has been an interest in the past few decades and has helped educators a lot in imparting knowledge to their students. And so we can see that LMS will be used a lot in the not so far away future. From this paper, we hope that our idea can be a potential researching material for the researchers.